William Chamberlayne account book - Chamberlayne, William
Account book containing fragmentary accounts reflecting Chamberlayne's gaming activities and the management of his estate.
Photocopies.
Plantation owner of New Kent County, Va.
Collection material in English.
Keywords: Agriculture -- Virginia -- New Kent County; Gambling -- Virginia -- New Kent County; Plantations -- Virginia -- New Kent County; New Kent County (Va.) -- History; New Kent County (Va.) -- Social life and customs; Virginia -- History -- 1775-1865.; Virginia -- Social life and customs; Plantation owners